(untitled) (Global Journal of Human-Social Science, 2023)
Over the years many youths have been targeted by politicians for votes in general elections due to their large numbers However they youths have always scored dismally in terms of turning up to elect leaders of their choice in various political positions Existing voting patterns have shown that the majority of the youth participate in political campaigns both on social media platforms and in the field but rarely in the voting process Notwithstanding the numerous civic education campaigns organized to foster voter registrations prior to elections less than 60 of the youth turn up for registration as voters Using Roger Hart 1992 conceptual model on level of participation and the normative democracy theory this paper used a critical review of existing literature interviews and observations for the just concluded 2022 Kenya s general elections We examine how e-voting can be employed as a strategy to influence the youths voting processes during general elections Document analysis and interviews were done and the findings are presented in the inform of narratives and excerpts